Ascites and abdominal pseudocyst: two uncommon ventriculoperitoneal shunt complications in two cases - (:unkn) unknown (TURKISH J PEDIATRICS, 2013)
Ascites and abdominal pseudocysts (APC) are two rare complications that can occur following placement of a ventriculoperitoneal (VP) shunt. Both complications are characterized by abnormal intraperitoneal cerebrospinal fluid (CSF) collections. Although various factors have been implicated, the exact pathogenesis of the two conditions remains elusive. This paper presents two cases of VP shunt placement resulting from hydrocephaly. The first patient presented with generalized ascites and the other with APC, both of whom were six years old. APC and ascites after VP shunt placement are rare and distinct conditions; therefore, they may require different management strategies.
Keywords: abdominal pseudocysts; ascites; ventriculoperitoneal shunt; cerebrospinal fluid; child; HYDROCEPHALUS; MANAGEMENT